PWE-002 Evaluating the role of MR enterography in the management of patients with crohns disease. (8th June 2018) - Ahmed, Wafaa; Kawa, Bhavin; Baruah, Gautom; Ghosh, Sukanya; Warner, Eleanor; Baburajan, Bijay
Abstract : Introduction: Magnetic resonance enterography (MRE) is widely available and is being increasingly utilised in the management of patients with Crohns disease (CD). Free of ionising radiation, it is particularly valuable in sequential imaging. In addition, it is an attractive, non-invasive option in the investigation of patients suspected to have small bowel CD. We sought to investigate whether MRE in patients with CD alters patient management as well as its utility in the diagnosis of CD. Methods: PACS was interrogated to identify patients undergoing MRE across two sites in a trust from March to April 2017. Unique patient IDs were cross referenced with Telepath, Allscripts and Endobase databases for demographic data, results of faecal calprotectin (FC) and clinical outcomes. MR protocol was standardised and calprotectin measurement has been available since 2016. Treatment change was defined as treatment initiation, escalation or cessation and referral for surgery. Patients being worked up for CD were those that had diarrhoea, abdominal pain or weight loss as their primary indication for MRE. Results: There were 111 MRE carried out over the 3 month period, mean age 38.2 (12–82), male 44 (39.6%), female 67 (60.4%).Of those 57 (51.3%) had established CD and 53 (47.7%) were for investigation of suspected CD. In this group, the results of the MRE influenced the management of 39 cases (68.4%) vs 18 (31.6%) with no change. 30 (52.6%) patients had a new treatment or treatment escalation, 6 (10.5%) had their treatment stopped and 3 (5.3%) were referred for surgery. 24 patients with CD had FC done within 2 months of MRE. Interestingly all of those with a FC <250 ug/g had a normal MRE (n=8). In patients being worked up for CD, 42 (79.2%) of the MREs were normal and 2 (3.7%) were highly suspicious for CD, the rest showed non-specific inflammation and other findings including liver haemangioma, cholecystitis, jejunal diverticulitis and a carcinoid tumour. Surprisingly, MRE was used as the initial investigation in 9 (16.9%) patients, in which there was one case of cholecytitis but the rest were negative. As in patients with CD, no patient with a FC <250 ug/g had a positive MRE. Conclusion: MRE results influence treatment decisions in CD, facilitating changes in management including withdrawal of biologics. It is seemingly ineffective as a diagnostic test for small bowel CD and calprotectin may be more useful in that context. This study is limited by the exclusion of patients with Crohn's disease who have not had MRE but these findings suggest potential cost savings if MRE is reserved for patients with CD suggested by other means such as faecal biomarkers or endoscopy.